Effect of subclinical hypothyroidism in women treated with levothyroxine on some hematological parameters and body mass index in relation to the age of the patients. (Journal of the College of Basic Education, 2022)
The current study was conducted on 40 control females, ages 40-50 years, while the patient group included 40 patients with subclinical hypothyroidism, ages less than 40 years (20 patients) and between 40-50 years (20) patients, and from reviews to the specialized center for endocrinology And diabetes near Al-Kindi Hospital / Al-Rusafa, Baghdad Governorate, and treatment with levothyroxine. The results showed a non-significant increase (P>0.05) in TSH levels for the age group less than 40 years, with an average mu / L (1.67 ± 6.28), as well as in the age group 40-50 years, with an average of 1.5 mu /L) ± (6.82) compared with the control group (4.07 ± 0.09mu/L), except that the values ​​of the TSH level in both groups of patients were higher than the normal values ​​of the TSH hormone